Influência do jejum durante o turno noturno de trabalho sobre o comportamento alimentar e metabolismo glicídico: ensaio clínico randomizado, cruzado e controlado - Teixeira, Bruno Simão (2022)
Recent studies have tested different nutritional strategies with the aim of minimizing the deleterious effects of food consumption at night by fixed night workers. However, there are many uncertainties about how food consumption should be during the night shift, whether the worker should really eat, and the possible effects of night consumption on food intake the next day. Objective: To investigate the influence of fasting during the night shift on dietary intake, metabolic and behavioral parameters the following day. Material and Methods: This trial was conducted on 10 male police officers who has been working at night for at least 2 years (age= 38.8±4.0 years old; BMI= 25.9±1.9kg/m²). Participants were tested under three different conditions separated by at least six days of washout in a randomized, crossover design: “Night Shift Fasting”- two nights of fasting during the night shift; “Night Shift Eating”- two nights with the consumption of a standardized meal equaling 30% of the energy requirement during the night shift; and “Nighttime Sleep”- two nights of sleep. The morning after the second day of each experimental condition, blood glucose and insulin and food perceptions were assessed, and food intake was assessed with an ad libitum test meal. To assess food intake throughout the day, the volunteers completed a food record over the 24 hours following the interventions. Generalized Estimating Equations (GEE) models were used to analyze the effect each of the interventions on the variables glucose, insulin, food perceptions and next-day dietary intake. Results: Food intake during the test meal, especially of proteins and fats, was higher after fasting during the night shift compared to the other conditions (p<0.05), whereas desire to eat scores were lower after the Night Shift Fasting compared to Night Shift Eating condition (p=0.043). Hunger levels were lower after the Night Shift Fasting compared to the Nighttime Sleep condition (p=0.012). Insulin and HOMA were also lower in the morning after Night Shift Fasting (p<0.001). Conclusions: Fasting during the night shift leads to a higher intake of energy and macronutrients both in the early morning after work and throughout the next day, but also lower insulin levels and HOMA in the morning. Food ratings indicative of a lower desire to eat were also observed after fasting during the night shift.